Promoting Critical Thinking through Cultural Topics in Bangladeshi Tertiary EFL Context - Mehrin, Iram (Journal of NELTA, 2020)
Promoting critical thinking among students has been a topic for extensive study for a long time. However, this is quite a new area of exploration and investigation in the Bangladeshi EFL context. This paper explores whether classroom activities on culture can work as effective incentives in promoting critical thinking in Bangladeshi tertiary level English language classes. Cultural topics were designed for the tertiary level English class and used accordingly for critical thinking in a class of 36 students in a private university of Dhaka, Bangladesh. Classwork and home assignments on different cultural topics were evaluated against a rubric of critical thinking, and at the end of the semester, an open-ended discussion-based interview was conducted. The gradual development of critical thinking among students was observed from the data gathered from both classes and interviews. Finally, the author presents implications for the EFL instructors, course designers, and book writers regarding the modifications required in the topics and teaching style to promote the development of critical thinking among the Bangladeshi tertiary level EFL students.